Effect of bay laurel (Laurus nobilis) extract as prebiotic on growth and food conversion of common carp (Cyprinus carpio) - Taher, Majid M.; Al-Niaeem, Khalidah S.; Al-Saad, Safaa A. (Iraqi Journal of Aquaculture, 2021)
Effect of prebiotic, bay laurel’s (Laurus nobilis) leaf extract, on growth, food conversion and survival of common carp (Cyprinus carpio) was studied in the laboratory. Three concentrations (1% T1, 2% T2 and 3% T3) in addition to control (0%) were used in eight aquaria with two replicates. Experiment was conducted between 1 February to 4 May, 2016 including 21 days for acclimation. Results appeared that highest weight increment (7.63 g) achieved by T2 compared with the lowest (5.42 g) that achieved by control. Results also appeared that no fish mortalities occurred during experiment. Better food conversion (4.56) achieved by T2 compared with 6.59, 5.46 and 5.2 for control, T1 and T3 respectively. Highest daily growth rate (0.099 g/day) was achieved by T2 comparing with (0.07, 0.078 and 0.081) g/day achieved by control, T1 and T3 respectively. Highest specific growth rate (0.975 %/day) was achieved by T2 comparing with other treatments. It was concluded that better results achieved by T2 that 2% of laurel leaf extract was added to fish food.